Certain topological indices and polynomials for semitotal line graph and its line graph for Dutch windmill graph - Kanwal, Salma; Rauf, Asia; Malik, Shabnam; Sumbal, Tahira; Arshad, Misbah; Irfan, Rida; Manzoor, Ayesha (Utilitas Mathematica, 2020)
Dutch windmill graph [1,2] and denoted by Dnm Order and size of Dutch windmill graph are (n - 1) m + l and mn respectively. In this paper, we computed certain topological indices and polynomials i.e. Zagreb polynomials, hyper Zagreb index, Redefined Zagreb indices, modified first Zagreb index, Reduced second Zagreb index, Reduced Reciprocal Randic index, 1st Gourava index, 2nd Gourava index, 1st hyper Gourava index, 2nd hyper Gourava index, Product connectivity Gourava index, Sum connectivity Gourava index, Forgotten index, Forgotten polynomials, M-polynomials and some topological indices in terms of M-polynomials i.e. 1st Zagreb index, 2nd Zagreb index, Modified 2nd Zagreb index, Randić index, Reciprocal Randić index, Symmetric division index, Harmonic index, Inverse Sum indeg index, Augmented Zagreb index for the semitotal line graph and line graph of semitotal line graph for Dutch windmill graph. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.